Hepatocyte-derived microRNAs as sensitive serum biomarkers of hepatocellular injury in Labrador retrievers. (May 2016) - Dirksen, K.; Verzijl, T.; van den Ingh, T.S.G.A.M.; Vernooij, J.C.M.; van der Laan, L.J.W.; Burgener, I.A.; Spee, B.; Fieten, H.
Highlights: HDmiR levels in serum can be used to detect hepatocellular injury. HDmiR levels have superior sensitivity over ALT activity in detecting liver injury. Labradors with high hepatic copper concentrations have elevated serum miR-122 levels. Circulating miR-122 serum levels correlate with ALT activity in Labrador retrievers. Abstract: Common parenchymal liver diseases in dogs include reactive hepatopathies and primary hepatitis (acute or chronic). In chronic hepatitis, there is usually a long subclinical phase. Specific clinical signs become overt only when liver damage is severe and in this phase, treatment is usually less effective. Limited data are available regarding the sensitivity of liver enzyme activity or biomarkers for early detection of subclinical hepatitis. Hepatocyte-derived microRNAs (HDmiRs) were recently identified as promising biomarkers for hepatocellular injury in multiple species. Here, the potential of the HDmiRs miR-122 and miR-148a as sensitive diagnostic biomarkers for hepatocellular injury in Labrador retrievers was investigated. Samples from 66 Labrador retrievers with histologically normal livers, high hepatic copper, and with various forms of liver injury were evaluated for serum alanine aminotransferase (ALT) activity and microRNA values. Median values of HDmiR-122 were 34.6 times higher in dogs with liver injury and high ALT than in normal dogs (95% confidence intervals [CI], 13–95; P < 0.001). HDmiR-122 values were significantly increased in dogs with liver injury and normal ALT (4.2 times; 95% CI, 2–12; P < 0.01) and in dogs with high hepatic copper concentrations and unremarkable histopathology (2.9 times; 95% CI, 1.1–8.0; P < 0.05). Logistic regression analyses demonstrated that miR-122 and miR-148a were both predictors of hepatocellular injury. The sensitivity of miR-122 was 84% (95% CI, 73–93%), making it superior to ALT (55%; 95% CI, 41–68%) for the detection of hepatocellular injury in Labrador retrievers ( P < 0.001). This study demonstrated that serum HDmiR, particularly miR-122, is a highly sensitive marker for the detection of hepatocellular injury in Labrador retrievers and is a promising new biomarker that may be used for early detection of subclinical hepatitis in dogs.